Mitochondrial DNA T to G mutation 8993 in Leigh encephalopathy and organic aciduria - Ueno, M; Oka, A; Maegaki, Y; Toyoshima, M; Fujiwaki, T; Takeshita, K (No to hattatsu, 2001)
We report a 10-month-old female infant with Leigh encephalopathy caused by a T to G mutation at nucleotide 8993 of mitochondrial DNA. Initial manifestations were diarrhea and pyrexia, followed by disturbance of consciousness. Blood chemistry showed lactic acidosis, and cranial T2 weighted magnetic resonance imaging demonstrated symmetric high-intensity areas in the basal ganglia, consistent with Leigh encephalopathy. Analysis of urinary organic acids revealed a increase of alpha-ketoglutamate. Derivatives of branched chain amino acids, which accumulate in maple syrup disease, were also increased. Lipoamide dehydrogenase (E3) deficiency was initially suspected; however, normal activity of pyruvate dehydrogenase complex excluded the diagnosis. The organic aciduria disappeared after two weeks. The CNS lesions in our case were observed more prominently in the floor of the bilateral frontal lobes than in the globus pallidus and putamen. In this case, mitochondrial DNA mutation may have caused organic aciduria and the atypical imaging findings.